Energy consumption in an ageing population: exploring energy use and behaviour of low-income older Australians. (September 2017) - Romanach, Lygia; Hall, Nina; Meikle, Sarah
Abstract: This paper explores energy use and behaviour of older urban Australians by identifying the key factors that shape their energy demand. As Australia is facing an aging population, understanding what structural and behavioural factors can help improve residential energy efficiency is key for developing effective policy initiatives to support the successful management of household energy costs, wellbeing and carbon emissions within this population. This paper reports on survey and electricity meter data collected for an energy efficiency program involving 1, 647 older householders (aged 60 and above) living within the Brisbane City Council Local Government Area. The program was funded by the Australian Government Low-Income Energy Efficiency Program (LIEEP) and ran from November 2013 to February 2015. Brisbane is Australia's third largest city and has a subtropical climate, with warm or hot weather for most of the year. The findings show that electricity consumption within the study's sample population was influenced by both structural and demographic factors. These factors include range of energy sources used, number of bedrooms and number of people living in the household, as well as type of appliances used in the home. In terms of appliance use, high-energy consuming appliances such as water heating and space cooling systems, clothes-dryers and refrigerators were important predictors of energy consumption. Over two-thirds of the study participants were relying on cooling systems for thermal comfort, and such systems were typically not being used in an energy efficient way. The use of high-energy demand heating and cooling systems can account for around 40% of energy consumption in Australian households, and has a large impact on electricity peak demand. With the penetration of air-conditioning in seniors' home expected to increase over time, it is important to better understand the range of low and high-energy demand practices that are currently employed by older Australians to achieve thermal comfort at home. Designing strategies that minimise the need for high-energy demand cooling practices will be key for managing household energy costs and wellbeing within this target audience.